Anime intersections : tradition and innovation in theme and technique - Cavallaro, Dani, 1962- (Jefferson, N.C. : McFarland, 2007)
"The main body of the text comprises nine chapters, each of which is a detailed analysis of a production and explores the developments in works such as Ninja Scroll, Perfect Blue, and Howl's Moving Castle. The final chapter examines the impact of the medium within Western contexts"--Provided by publisher.
Includes bibliographical references (p. 199-205) and index.
Includes filmography: p. 187-194.
Keywords: Animated films -- Japan -- Themes, motives